CLASSIFICATION AND DIAGNOSTICS OF ANEMIA IN CHILDREN - A. G. Rumyantsev ("Paediatrician" Publishers LLC, 2011)
Anemia in children is one of the most frequent somatic diseases. Criteria of anemia diagnosis are strictly regulated as decrease of hemoglobin/erythrocytes level accompanies majority of infectious, inflammatory, autoimmune, hereditary diseases and, in several cases, it is estimated as transitory disease in some periods of children's growth and development. The article presents main classification and differential diagnostic schemes of anemia. Diagnostics makes accent on laboratory analysis; they are the basis of differential diagnosis and differential therapy of anemia in children.